PENGARUH ALAT PERMAINAN EDUKATIF DALAM MENINGKATKAN KONSENTRASI DAN MOTORIK HALUS ANAK ADHD (ATTENTION DEFICIT HYPERACTIVITY DISORDER) - Hardaningtyas, Khoirunisa; Moewardi, Istar; Ananta, Juwitas Putri; Ananta, Juwita Putri (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2024)
One of the classifications of children with special needs (ABK) is behavioral disorders or ADHD. ADHD (Attention Deficit Hyperactivity Disorder) is a medical condition characterized by difficulty in focusing attention, hyperactivity and or impulsivity that is more frequent and severe than that of children of the same age. ADHD children experience barriers in concentration and fine motor skills. Efforts that can be made to improve concentration and fine motor skills of ADHD children are by using educational game tools. The purpose of this study is to examine the effect of educational game tools in improving concentration and fine motor skills of ADHD (Attention Deficit Hyperactivity Disorder) children. This research uses the literature study research method. Data were collected by looking for previous research relevant to the effect of educational game tools in improving concentration and fine motor skills of ADHD children. The collected data were analyzed using content analysis techniques. The results of the literature study from previous studies showed that ADHD children showed a positive response by being able to focus on doing something for a long duration and improved fine motor skills after using educational game tools. The conclusion of this study is that the use of educational game tools can improve concentration and fine motor skills of ADHD children.